2017
DOI: 10.4103/1008-682x.178850
|View full text |Cite
|
Sign up to set email alerts
|

Strong association of SLC1A1 and DPF3 gene variants with idiopathic male infertility in Han Chinese

Abstract: Male infertility is a multifactorial syndrome encompassing a wide variety of disorders. In recent years, several genome-wide single-nucleotide polymorphism (SNP) association studies (GWAS) have been performed on azoospermia and/or oligozoospermia in different populations including two GWAS on nonobstructive azoospermia in China; however, the association of SNPs with idiopathic male infertility, especially asthenozoospermia and oligozoospermia, and their correlation with semen parameters are still not clear. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Liu et al 49 have reported that five SNPs (rs215702, rs6476866, rs10129954, rs2477686 and rs10841496) were significantly correlated with sperm progressive motility. However, present study did not detect the variants associated with sperm motility including the region 400 kb upstream and downstream of these five SNPs.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al 49 have reported that five SNPs (rs215702, rs6476866, rs10129954, rs2477686 and rs10841496) were significantly correlated with sperm progressive motility. However, present study did not detect the variants associated with sperm motility including the region 400 kb upstream and downstream of these five SNPs.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the power was reduced in our sub-phenotype analyses as a consequence of a decrease in the cohort sizes. Therefore, The association of PEX10-rs2477686 with male infertility and NOA was replicated by Gu et al 35 and Liu et al, 39 although additional replication efforts did not confirm this NOA-associated signal.…”
Section: Detection Of Covid-19 In the Male Reproductive Tractmentioning
confidence: 95%
“…Furthermore, the sample size of our study cohort was in the same range of the large replication studies in Asian populations already published. [35][36][37][38][39] However, it should be noted that the sub-phenotype analyses were performed in lower study cohorts, which reduced considerably the statistical power. Moreover, all the associations described here would be lost if multiple testing correction were applied.…”
Section: Detection Of Covid-19 In the Male Reproductive Tractmentioning
confidence: 99%